Neonatal diabetes mellitus around the world: Update 2024 - Fabrizio Barbetti; Asma Deeb; Shigeru Suzuki (Journal of Diabetes Investigation)
Abstract Neonatal diabetes mellitus (NDM), defined as diabetes with an onset during the first 6 months of life, is a rare form of monogenic diabetes. The initial publications on this condition began appearing in the second half of the 1990s and quite surprisingly, the search for new NDM genes is still ongoing with great vigor. Between 2018 and early 2024, six brand new NDM‐genes have been discovered (CNOT1, FICD, ONECUT1, PDIA6, YIPF5, ZNF808) and three genes known to cause different diseases were identified as NDM‐genes (EIF2B1, NARS2, KCNMA1). In addition, NDM cases carrying mutations in three other genes known to give rise to diabetes during childhood have been also identified (AGPAT2, BSCL2, PIK3R1). As a consequence, the list of NDM genes now exceeds 40. This genetic heterogeneity translates into many different mechanism(s) of disease that are being investigated with state‐of‐the‐art methodologies, such as induced pluripotent stem cells (iPSC) and human embryonic stem cells (hESC) manipulated with the CRISPR technique of genome editing. This diversity in genetic causes and the pathophysiology of diabetes dictate the need for a variety of therapeutic approaches. The aim of this paper is to provide an overview on recent achievements in all aspects of this area of research.